Introducing Plant Parts and Their Functions Through Illustrated Flashcard Media for Fourth Grade Students at SD Negeri 4 Manukaya - Afri Ani Ul Azizah; Ni Wayan Sri Darmayanti (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to improve students' understanding of plant parts and their functions through the use of illustrated flashcards among fourth-grade students at SD Negeri 4 Manukaya. The study was motivated by students' low level of understanding, which was attributed to conventional teaching methods and the limited use of engaging instructional media. The research employed the ADDIE instructional design model, consisting of five stages: analysis, design, development, implementation, and evaluation. The participants were 19 fourth-grade students. The findings indicate that the use of illustrated flashcards enhanced students' classroom participation, learning interest, and conceptual understanding. This was reflected in increased student engagement during the learning process and evaluation results showing that most students achieved scores above the Minimum Mastery Criterion (MMC). In addition, the flashcard media had positive effects on students' cognitive, affective, and psychomotor learning outcomes. Therefore, it can be concluded that illustrated flashcards are an effective instructional medium for improving students' understanding of plant parts and their functions.